Pelaksanaan Pembelajaran Tatap Muka Di SMK Kristen 1 Surakarta Pada Era New Normal - Taufik Aditya Ramadhan (Politeknik Kampar, 2023)
The aims of this study were to: (1) Find out how the implementation of face-to-face learning at SMK Kristen 1 Surakarta in the new normal era. (2) Knowing the obstacles faced in the implementation of face-to-face learning at SMK Kristen 1 in the new normal era. (3) Knowing the solution to overcome the obstacles in the implementation of face-to-face learning at Christian Vocational High School 1 in the new normal era. This research is a qualitative descriptive study. Sources of data used in this research are informants, places and events, and documentation. The sampling technique used is purposive and snowball sampling. Data collection techniques used are interviews, observation and documentation. The validity of the data used is source triangulation and method triangulation. While the data analysis used is an interactive analysis model.The results of the study: (1) The implementation of face-to-face learning at SMK Kristen 1 Surakarta has been well organized and guided by government regulations, for initial preparations to form an internal Covid-19 task force team, licensing the local education office, notification to parents containing SOPs as technical face-to-face learning and held a limited face-to-face learning simulation which was attended by several students who had been vaccinated together with BK teachers and the local covid-19 task force. For its implementation, the curriculum used is a simplified curriculum by shortening the duration of learning. Procurement of facilities according to health protocols as another mandatory preparation. Meanwhile, for evaluation during PTM there is a reduction in the duration of learning and the advantages of PTM, students absorb more material during face-to-face learning. (2) The obstacle felt by SMK Kristen 1 Surakarta is the difficulty in inculcating the habit of wearing masks correctly while at school. (3) Coordinate with parents, the Covid task force team and also teachers to remind each other and provide direction for students who violate.